2002
DOI: 10.1038/nsb804
|View full text |Cite
|
Sign up to set email alerts
|

The hsp70 chaperone DnaK is a secondary amide peptide bond cis-trans isomerase

Abstract: Peptidyl prolyl cis-trans isomerases can enzymatically assist protein folding, but these enzymes exclusively target the peptide bond preceding proline residues. Here we report the identification of the Hsp70 chaperone DnaK as the first member of a novel enzyme class of secondary amide peptide bond cis-trans isomerases (APIases). APIases selectively accelerate the cis-trans isomerization of nonprolyl peptide bonds. Results from independent experiments support the APIase activity of DnaK: (i) exchange crosspeaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 32 publications
1
79
0
2
Order By: Relevance
“…Surprisingly, in the full-length, lipomodified PrsA, the active site mutations did not disturb the catalysis of proline-limited folding in vitro, suggesting that PrsA also facilitates protein folding by some other mechanism than catalyzing the cis/trans isomerization of prolyl peptide bonds. It has recently been shown that the DnaK chaperone catalyzes the cis/trans isomerization of nonprolyl peptide bonds (43). The difference of activity between soluble and lipomodified mutant proteins may reside in the pattern of multimerization or protein-protein association of PrsA monomers.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, in the full-length, lipomodified PrsA, the active site mutations did not disturb the catalysis of proline-limited folding in vitro, suggesting that PrsA also facilitates protein folding by some other mechanism than catalyzing the cis/trans isomerization of prolyl peptide bonds. It has recently been shown that the DnaK chaperone catalyzes the cis/trans isomerization of nonprolyl peptide bonds (43). The difference of activity between soluble and lipomodified mutant proteins may reside in the pattern of multimerization or protein-protein association of PrsA monomers.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial Hsp70 DnaK was shown to catalyze this so-called APIase reaction (for amide peptide bond cistrans isomerase), but it is unknown whether this is a general activity of Hsp70 proteins (Schiene-Fischer et al 2002).…”
Section: Ppismentioning
confidence: 99%
“…The disaggregation mechanism involves a sequential action, first of ClpB modifying the surface of large compact aggregates thus increasing DnaK affinity, and second, of DnaK binding and unfolding entangled polypeptides, which accelerates cis-trans isomerizations in secondary amide bonds of refolding polypeptides (12,13). The efficiency of chaperone-mediated disaggregation strongly depends on the nature of the protein, on the aggregate size, and its solubility (4,10,11).…”
mentioning
confidence: 99%